trans-dominant interference with virus infection at two different stages by a mutant envelope protein of Friend murine leukemia virus. - Matano, T (1993)
A dominant negative mutant Friend murine leukemia virus (FMLV) env gene was cloned from an immunoselected Friend erythroleukemia cell. The mutant env had a point mutation which resulted in a Cys-to-Arg substitution at the 361st amino acid in the FMLV envelope protein (Env). The mutant Env was retained in the endoplasmic reticulum (ER) and accumulated because of its slow degradation. The NIH 3T3 cells expressing the mutant env were resistant to ecotropic Moloney MLV (MoMLV) penetration, suggesting that the mutant Env traps the ecotropic MLV receptors in the ER. When the mutant env gene was transfected into and expressed in the cells persistently infected with MoMLV, the wild-type Env was trapped in the ER, and the MoMLV production was suppressed. Thus, the mutant Env accumulating in the ER trans-dominantly and efficiently interfered with the ecotropic MLV infection at both the early and the late stages.